2018
DOI: 10.3747/co.25.3884
|View full text |Cite
|
Sign up to set email alerts
|

Complementary and Alternative Medicine Use in Patients Before and After a Cancer Diagnosis

Abstract: Use of cam, particularly biologic products, increased significantly after a cancer diagnosis. Further studies are required to examine the effect of cam use on the efficacy and safety of cancer therapies.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

11
118
0
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
3
3
1

Relationship

0
7

Authors

Journals

citations
Cited by 162 publications
(142 citation statements)
references
References 35 publications
11
118
0
2
Order By: Relevance
“…First, the research only chooses to confirm the diagnosis of Western medicine at a single regional hospital, as well as the patients who also receive the CHM treatment in outpatient and consultation. Alternative therapies are common in the United States (45.0-51.8%) [19,32] and Norwegian (33.8%) [33]. ere were 27.48% CHM users in this study; in contrast, only 12-20% of colon cancer patients in the NHIRD database receive CHM treatment [34].…”
Section: Discussionmentioning
confidence: 58%
“…First, the research only chooses to confirm the diagnosis of Western medicine at a single regional hospital, as well as the patients who also receive the CHM treatment in outpatient and consultation. Alternative therapies are common in the United States (45.0-51.8%) [19,32] and Norwegian (33.8%) [33]. ere were 27.48% CHM users in this study; in contrast, only 12-20% of colon cancer patients in the NHIRD database receive CHM treatment [34].…”
Section: Discussionmentioning
confidence: 58%
“…The desire to try everything, and take a chance on what might work is overwhelmingly tempting even for patients with a significant medical background. One study found that the most prevalent reason for CAM use was "just trying to do everything that can help" (11,12). Internet and social media provides an opportunity for patients to gain information and form opinions which guide their treatment decisions (13).…”
Section: Cam Awarenessmentioning
confidence: 99%
“…Disclosure is higher for women than for men and more likely in patients with a life-threatening illness (18). Furthermore, patients seek CAM information more from family, friends, and the internet than from health care providers (11,20).…”
Section: Cam Awarenessmentioning
confidence: 99%
See 2 more Smart Citations